Nineteenth-Century Media and the Construction of Identities - Brake, Laurel. author. aut Link
XV, 387 p.
Keywords: This collection of important new research in 19th-century media history represents some salient, recent developments in the field. Taking as its theme, the ways the media serves to define identities - national, ethnic, professional, gender, and textual, the volume addresses serials in the UK, the US, and Australia. High culture rubs shoulders with the popular press, text with image, feminist periodicals and masculine, gay, and domestic serials. Theory and history combine in research by scholars of international repute.